WAYS OF IMPLEMENTING FOREIGN EXPERIENCE IN LEGAL AND ORGANIZATIONAL SUPPORT OF ENTREPRENEURIAL ACTIVITIES IN THE SPHERE OF AGRICULTURE (Bulletin of criminological association of Ukraine, 2025)
Foreign experience in legal and organizational support for entrepreneurial activity in the agricultural sector serves as a guideline for the modernization of domestic agrarian policy. Its adaptation to Ukrainian conditions is one of the key factors in ensuring economic stability, social development of rural areas and further integration into the European space. This article analyzes the experience of European countries in the context of monitoring and transparent administration of state support for agricultural producers, which is carried out at the expense of budgetary resources. We believe that in Ukraine there is a need to create a separate body or department that would carry out independent management and control over state spending in agriculture, in particular regarding subsidies, grants, compensations, etc. In addition, the need is emphasized to begin today to prepare the legislative and administrative framework necessary for the future implementation of CAP mechanisms. This is not only about the general harmonization of the regulatory framework with the EU acquis, but also about the development of laws and by-laws that will regulate: procedures for providing, distributing and controlling state support for agricultural producers, mechanisms for recording and verifying data, creating electronic registers and digital platforms for administration, and reporting and accountability systems for executive bodies. The experience of creating various partnerships and networks is relevant, which could become the basis for forming a stable legal and organizational environment aimed at supporting agricultural innovations. Germany's experience in creating agricultural cooperatives also looks interesting for Ukraine. The transition from a narrow-sector to a unified approach in the legal regulation of cooperatives seems promising, which would simplify law enforcement practice, ensure greater integration into the European space, and create the prerequisites for the sustainable development of the cooperative movement. Also noteworthy is the experience of the United States in clearly planning the strategic development of agriculture and taking these plans into account each year in the state budget.
Keywords: foreign experience; implementation; agriculture; entrepreneurship; legal and organizational support